Cropland redistribution to marginal lands undermines environmental sustainability. Issue 1 (22nd May 2021) - Kuang, Wenhui; Liu, Jiyuan; Tian, Hanqin; Shi, Hao; Dong, Jinwei; Song, Changqing; Li, Xiaoyong; Du, Guoming; Hou, Yali; Lu, Dengsheng; Chi, Wenfeng; Pan, Tao; et al.
ABSTRACT: Cropland redistribution to marginal land has been reported worldwide; however, the resulting impacts on environmental sustainability have not been investigated sufficiently. Here we investigated the environmental impacts of cropland redistribution in China. As a result of urbanization-induced loss of high-quality croplands in south China (∼8.5 t ha –1 ), croplands expanded to marginal lands in northeast (∼4.5 t ha –1 ) and northwest China (∼2.9 t ha –1 ) during 1990–2015 to pursue food security. However, the reclamation in these low-yield and ecologically vulnerable zones considerably undermined local environmental sustainability, for example increasing wind erosion (+3.47%), irrigation water consumption (+34.42%), fertilizer use (+20.02%) and decreasing natural habitats (−3.11%). Forecasts show that further reclamation in marginal lands per current policies would exacerbate environmental costs by 2050. The future cropland security risk will be remarkably intensified because of the conflict between food production and environmental sustainability. Our research suggests that globally emerging reclamation of marginal lands should be restricted and crop yield boost should be encouraged for both food security and environmental benefits. Abstract : Widespread loss of high-quality cropland induced by urbanization and increasing shift of crop production to low-quality marginal land threaten food security and environmental sustainability.